2019
DOI: 10.1096/fj.201901816r
|View full text |Cite
|
Sign up to set email alerts
|

Enhancer of zeste homolog 2 modulates oxidative stress‐mediated pyroptosis in vitro and in a mouse kidney ischemia‐reperfusion injury model

Abstract: contributed equally to this work.Abbreviations: AKI, acute kidney injury; ALK5, activin receptor-like kinase; ASC, apoptosis-associated speck-like protein containing a caspase-recruitment domain; BUN, blood urea nitrogen; Cr, creatinine; EZH2, enhancer of zeste homolog 2; FLICA, fluorescent-labeled inhibitors of caspases; H/R, hypoxia/reoxygenation; H3K27me3, histone H3 lysine 27 trimethylation; HK-2, human renal proximal tubular epithelial cell line; I/R, ischemia/reperfusion; IL-1β, interleukin-1beta; LDH, l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 41 publications
(130 reference statements)
0
28
0
Order By: Relevance
“…Pyroptosis, characterized by excessive cell death and inflammation, is a specific cell death program distinct from apoptosis and necrosis (Miao et al, 2010). In this study, we found the injury induced by I/R and OGD/R resulted in excessive TEC death, which always went with pyroptosis in renal IRI (Tajima et al, 2019;Wang et al, 2019;Liu et al, 2020). As the main executor of cell pyroptosis, GSDMD, is widely expressed in different cells and tissues (Shi et al, 2015;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Pyroptosis, characterized by excessive cell death and inflammation, is a specific cell death program distinct from apoptosis and necrosis (Miao et al, 2010). In this study, we found the injury induced by I/R and OGD/R resulted in excessive TEC death, which always went with pyroptosis in renal IRI (Tajima et al, 2019;Wang et al, 2019;Liu et al, 2020). As the main executor of cell pyroptosis, GSDMD, is widely expressed in different cells and tissues (Shi et al, 2015;Liu et al, 2016).…”
Section: Discussionmentioning
confidence: 71%
“…It forms pores in the plasma membrane that ultimately cause cell swelling, membrane lysis, and inflammatory cytokines release (Shi et al, 2015). GSDMD-mediated pyroptosis of renal TECs is an essential process in renal ischemia-reperfusion (I/R) injury (Diao et al, 2019;Tajima et al, 2019;Liu et al, 2020). Thus, studies are needed to determine the biological networks involved in GSDMD-mediated pyroptosis in TEC injury induced by renal IR.…”
Section: Introductionmentioning
confidence: 99%
“…IP3R1 expression is increased in H/R injury of spinal cord white matter 9 . Recent studies have shown that cell pyroptosis is related to I/R injury 22,29 . Pyroptosis is defined as a Caspase-1-dependent mechanism, and NLRP3 is indispensable for the activation of Caspase-1 30,31 .…”
Section: Discussionmentioning
confidence: 99%
“…ROS Production Detection. The ROS levels were determined based on our previous study [16] through the commercial kit instruction (Nanjing Jiancheng, China). The samples were incubated with dichloro-dihydro-fluorescein diacetate (20 μM) at room temperature for 30 min, and the result of the ROS level was quantified through flow cytometry.…”
Section: Measurement Of Malondialdehyde (Mda) Andmentioning
confidence: 99%